New records of genus Volvariella (Pluteaceae) from Cuc Phuong National Park - Huyen Thanh Le; Ngoc Thi Chu (Vietnam Journal of Science, Technology and Engineering, 2018)
Cuc Phuong National Park is a natural reserve located in Ninh Binh, Hoa Binh and Thanh Hoa provinces. Cuc Phuong is Vietnam’s oldest National Park and also is one of the most important sites for biodiversity in Vietnam. Little is known about the diversity of macrofungi in this special area. This paper presents the collecting process of fungal samples and the identification and description of some fungal species belonging to the genus Volvariella (Pluteaceae) based on the morphological characteristics in Cuc Phuong National Park, Ninh Binh province. This study identified 5 species including Volvariella murinella, Volvariella gloiocephala, Volvariella volvaceae, Volvariella taylorii, and Volvariella pusilla. Interestingly, of them, 4 macrofungus species were first recorded at this National Park.